Firearm-related Abuse and Protective Order Requests Among Intimate Partner Violence Victims - Lynch, Kellie R. (Journal of interpersonal violence, 2022)
Firearms play a critical role in the murder of intimate partner violence (IPV) victims and there is evidence that laws prohibiting protective order (PO) respondents from possessing a firearm reduce IPV fatalities. However, little research has compared specific abuse tactics involving firearms among victims who have and have not sought a PO against an abuser. This study investigates IPV victims? experiences with a range of firearm-related abuse tactics across victim race/ethnicity, in addition to the relationship between firearm IPV and PO requests, above and beyond IPV not involving firearms. Questionnaires were administered to 215 female victims recruited from six domestic violence shelters in Texas. Over one-half of victims who sought a PO were threatened to be shot by their abuser and victims who experienced high levels of firearm abuse incurred a 302% increase in the odds of requesting a PO. There were no significant differences between White, Black, and Hispanic victims regarding firearm IPV tactics. The results shed light on the magnitude of risk IPV victims can experience when seeking a PO against an abusive partner.